2014
DOI: 10.1007/s12010-014-1320-5
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of Horseradish Peroxidase Production Using a Transient Expression System in Nicotiana benthamiana

Abstract: Abstract:Despite the advantages of plant-based transient expression systems relative to microbial or mammalian cell systems, the commercial production of recombinant proteins using plants has not yet been achieved to any significant extent. One of the challenges has been the lack of published data on the costs of manufacture for products other than biopharmaceuticals. In this study, we report on the technoeconomic analysis of the production of a standard commercial enzyme, namely horseradish peroxidase (HRP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 26 publications
0
56
0
Order By: Relevance
“…Record yields up to 4.8 g/kg FW of anti‐idiotype antibodies have been reported using magnICON (Bendandi et al ., ). With our current, nonoptimized yields, a 1000 sqm greenhouse facility growing 15‐kg biomass/m 2 /year (Walwyn et al ., ) could produce up to 3000 1.0 gram doses per year. Further improvements in yield and formulation could reach 15 doses/m 2 /year as a reasonable scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Record yields up to 4.8 g/kg FW of anti‐idiotype antibodies have been reported using magnICON (Bendandi et al ., ). With our current, nonoptimized yields, a 1000 sqm greenhouse facility growing 15‐kg biomass/m 2 /year (Walwyn et al ., ) could produce up to 3000 1.0 gram doses per year. Further improvements in yield and formulation could reach 15 doses/m 2 /year as a reasonable scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for this include low upstream costs, ease of scalability and the lack of adventitious animal pathogens. Economic advantage, however, has not yet been proven in practice or in published studies to any appreciable extent (Walwyn et al ., ). Most of the cost of manufacturing proteins is associated with downstream processing, specifically purification and analytics.…”
Section: Competing Technologies and Potential Economic Impacts Of Pmpmentioning
confidence: 97%
“…To this end, we need a better understanding of the production costs of GRFT. Many theoretical studies have been performed examining the cost of goods of multiple products to demonstrate the economic feasibility of PMPs, all of which show that the economics is product, process and scale dependent (Tuse et al ., ; Walwyn et al ., ). Success of GRFT‐based commercial products is dependent on its performance in preclinical and clinical trials (safety and efficacy); however, practical issues regarding its availability as a sexual health product to a substantial population of potential users is contingent on the cost, which is driven in part by the production process.…”
Section: Introductionmentioning
confidence: 97%
“…One of the impacts of modeling is that it enables the costs of manufacturing to be evaluated with greater accuracy, which is necessary for the translation of laboratory processes into a commercial environment. Several costing studies have been reported recently, including those based on top-down analysis [47] and bottom-up approaches [48,49]. …”
Section: Upstream and Downstream Processes Engineeringmentioning
confidence: 99%